The Influence of Price, Endorser, and Location on Navi Wear Purchase Decisions - Luh Putu Nomy Cahyani; Made Setini; Bayu Pasupati (Asean International Journal of Business, 2026)
ABSTRACT This study aims to analyze the influence of price, celebrity endorser, and location on consumer purchase decisions at Navi Wear Clothing Store in Denpasar. This research is motivated by sales fluctuations and high competition in the fashion business in Denpasar City. The research method used was a quantitative approach with survey techniques through the distribution of questionnaires to 100 respondents who were selected using the purposive sampling method. The data obtained was analyzed using multiple linear regression with the help of the SPSS program. The results of the study show that partially price, celebrity endorser, and location have a positive and significant effect on consumer purchase decisions. In addition, simultaneously these three variables also have a positive and significant effect on consumer purchase decisions at Navi Wear Clothing Stores in Denpasar. The findings of this study show that the right pricing strategy, effective use of celebrity endorser, and strategic business location selection play an important role in improving consumer purchasing decisions.